ANALISIS KONTROL KUALITAS KOMPONEN TROMBOSIT : STUDI PERBANDINGAN METODE PEMBUATAN KOMPONEN TROMBOSIT - Eva Ayu Maharani; Dewi Astuti (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2022)
Platelet components for transfusion are classified by various techniques or types of blood bags, namely manual centrifugation (Tc-Tr, Tc-Qd, Tc-Bc) and apheresis (Tc-Ap). The effectiveness of the use of these components is assessed through internal quality control. This study aimed to determine the quality of the platelet components with the examination of pH, volume, platelet count, and leukocyte count. Platelet index (MPV, PDW, and P-LCR) was performed as an additional examination. The research data were analyzed based on PMK No. 91, 2015 standard. The difference test was performed between manual centrifugation techniques (Tc-Tr, Tc-Qd, Tc-Bc) and apheresis (Tc-Ap) with p-value < 0,05. The results of the analysis showed that the parameters of pH, volume, and the number of leukocytes were by the standard, except for the number of platelets in the components of Tc-Tr and Tc-Qd. MPV and PDW values tend to be low and P-LCR values are generally normal. This can indicate that the platelet component is generally not in an activated state. The conclusion of this study, the Tc-Ap component is the best platelet component with quality control that is not significantly different from the Tc-Bc component.